Effect of elements Zn, Sn and In on microstructures and performances of AZ91 alloy - 于湛 赵红阳 胡小东 巨东英 (Transactions of Nonferrous Metals Society of China, 2010)
A new magnesium alloy plate added elements Zn, Sn and In was manufactured by twin-roll continuous casting method to improve the precipitation of AZ91 alloy. The effects of elements addition and casting method on microstructure and mechanical properties of the Mg-Zn-In-Sn alloys were investigated by optical microscopy （OM）, transmission electron microscopy （TEM）, electron probe micro-analysis （EPMA）, X-ray diffractometry （XRD） and energy dispersion spectrograph （EDS）. The results show that the Mg-Zn-In-Sn alloy has higher tensile strength and better corrosion protection than the AZ91 alloy. The outstanding precipitation strengthening effect of the alloy is attributed to the small grain size and the hard precipitates between the grain boundaries.